NET PROFITABILITY ANALYSIS OF TRAVEL ORGANIZERS AND TRAVEL AGENCIES - Subačienė, Rasa; Senkus, Kastytis (Ekonomika, 2013)
Abstract. Evaluation of financial position and operating effectiveness of a company is a relevant problem Therefore, separate aspects of a company’s activity may be measured in different approaches. The purpose of the article is to present the system of a pyramidal analysis of the net profitability ratio and to evaluate the net profitability of travel organizers and travel agencies. The research object was financial statements of travel organizers and travel agencies for the period 2009–2011. The methods used for this purpose were analysis of academic materials, financial statements of travel organizers and travel agencies, filing of information, comparison, and summarizing.